HUBUNGAN PENGETAHUAN REMAJA PUTRI TENTANG PERSONAL HYGIENE DENGAN CARA MELAKUKAN PERSONAL HYGIENE DENGAN BENAR SAAT MENSTRUASI DI MA HASANAH PEKANBARU - Yeni Devita; Nola Kardiana (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2018)
Physical problems that may arise from the lack of knowledge, is the lack of personal hygiene, because they do not have sufficient knowledge about the proper way to treat genetal organs so someone will be easy to behave that is harmful or indifferent to the health of genetic tools, and vice versa if someone who has knowledge of the way Proper genetal organ care will prefer to behave appropriately in maintaining the hygiene of the reproductive equipment (Dewi et al, 2013). The purpose of this study is to find out whether there is a Young Women Knowledge Relationship About Personal Hygiene With How To Perform Proper Personal Hygene During Menstruation At MA Hasanah Pekanbaru Year 2014. The type of this research is quantitative research with descriptive analytic design. The population of all students of MA Hasanah Pekanbaru, with a sample of 83 female students. The sampling technique is total sampling. The primary data collection is by using questionnaire. Univariate and bivariate data analysis. The results of the research have been found that the majority of knowledge is quite as much as 43 female students (51.8%). The steps of the majority respondents were negative amounted to 48 female students (57.8%). From the statistical test results obtained Pearson Chi-Square value with Pvalue = 0.013 and significant level = 0.05. This shows that Pvalue <0.05 means there is a meaningful relationship between Young Women Knowledge of Personal Hygiene by How To Perform Proper Personal Hygene During Menstruation At MA Hasanah Pekanbaru Year 2014. It is expected from the results of this study MA Hasanah school especially for students to know more About personal hygiene during menstruation.